Isolation of the Major Viral Glycoprotein and a Putative Precursor from Cells Transformed by Avian Sarcoma Viruses - Halpern, Michael S. (1974)
Immune precipitation with a monospecific antiserum was employed to study the synthesis of the major viral glycoprotein gp85. Labeled gp85 was detectable by polyacrylamide gel electrophoresis of immune precipitates prepared from lysates of transformed cells which had been labeled for long term with radioactive amino acid or fucose. When immune precipitates were prepared from lysates of cells pulse-labeled with radioactive amino acid, the bulk of the precipitated counts did not appear in gp85 but in a heterogeneous protein fraction with a mean molecular weight of approximately 70,000; this fraction has been designated p70. If, however, the pulse label was followed by incubation of the cells in medium containing excess unlabeled amino acid, the bulk of the precipitated counts comigrated with gp85. Similar pulse-labeling experiments with radioactive fucose and glucosamine suggested that p70 represents incompletely glycosylated precursor to gp85.